The prevalence of multi-drug-resistant staphylococcus aureus and klebsiella pneumoniae in cooked meat samples collected from hospital cafeterias in the Dhaka city corporation area - Hoque, Mahmuda; Mesbah, Afrina; Bala, Anik Shuvro (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.